Hemostatic Agents Used in the Field of Dentistry: An Overview - Sharmistha Das1 , Rashmita Nayak2 , Rinkee Mohanty3 , Anurag Satpathy2 , Saurav Panda4 , Prachi Khun (Institute of Medico-legal Publications Pvt Ltd, 2020)
Intraoperative or postoperative bleeding during any periodontal surgical procedure can to some seriouscomplications. Difficulties related to bleeding can be seen in both healthy individuals as well as bleedingdisorder patients, any systemic complications and patients under anticoagulant drug therapy. Having aclear perspective about the preventive measures to be taken to control the profuse bleeding is a must fora practitioner. The purpose of the literature review is to discuss the administration of different types ofhemostatic agents available for controlling bleeding.